Positive pole piece capable of inhibiting dissolution of transition metal, preparation method of positive pole piece and lithium ion battery
By adding tubular halloysite to high-nickel cathode materials, the problem of transition metal ion dissolution in lithium battery cathode materials is solved, and the long-term cycle stability and high energy density of the battery are achieved.
Patent Information
- Application Number
- CN202410556994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-01-24
AI Technical Summary
The dissolution of transition metal ions in the positive electrode material of lithium battery leads to mixed Li+/Ni2+, causing a drop in capacity and operating voltage and decay of cycling stability.
The natural one-dimensional nanotubular clay mineral tubular halloysite (HNT) is added to the high-nickel cathode material. Through its unique hollow tubular structure and high specific surface area, a cathode plate with the ability to inhibit the dissolution/crosstalk of transition metal ions is formed.
Effectively suppress the dissolution and bruises of transition metal ions, prevent the phase and micro -cracks of the positive pole material, and improve the long -term cycle stability of the battery.
Smart Images

Figure CN119361594A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a positive electrode sheet capable of inhibiting the dissolution of transition metals, a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of electric vehicles, smart electronic devices and other fields, there is an urgent need for high-energy-density lithium batteries with long cycle life and high safety. Using a positive electrode with high voltage and high specific capacity is an effective way to increase the energy density of batteries. Among them, high-nickel ternary layered positive electrode materials are expected to become the mainstream positive electrode materials for future power energy storage batteries due to their advantages of high energy density and high operating voltage.
[0003] However, there are many problems and challenges in the high temperature and high pressure cycle process: (1) The dissolution of transition metal ions will cause serious Li + / Ni 2+ Mixing phenomenon, the surface structure of the positive electrode changes from an ordered layered structure to a mixed phase such as spinel phase / rock salt phase, causing the capacity and working voltage to decrease and the cycle stability to decline; (2) Ni in the charged state 4+ It will catalyze the continuous oxidative decomposition of carbonate-based organic electrolytes, causing irreversible loss of the electrolyte and generating interfacial byproducts (CEI) with low ionic / electronic conductivity, which will increase the interfacial impedance. At the same time, the decomposition of the electrolyte is accompanied by the generation of trace amounts of H2O, which will cause further dissolution of transition metal ions and continuously reduce the cyclic performance of the material. (3) The uncontrollable crosstalk of transition metal ions will also cause the failure of the lithium metal negative electrode.
[0004] Due to the wide range and high requirements of energy applications, it is crucial to develop green, cheap, abundant and effective modified cathode materials. How to reduce the dissolution of transition metal ions in cathode materials is an urgent problem to be solved.
[0005] Chinese patent CN111200128A discloses a method for preparing a high-performance positive electrode material that inhibits the dissolution of transition metal ions in positive electrode materials for lithium-ion batteries, which specifically includes the steps of preparing a porous conductive polyamic acid dispersion containing an imidazole structure by in-situ polymerization, preparing a lithium-ion positive electrode material coated with polyamic acid having a porous conductive structure, and preparing a lithium-ion positive electrode material coated with a porous conductive polyimide containing an imidazole structure. This patent is to prepare a lithium-ion positive electrode material coated with a porous conductive polyimide containing an imidazole structure, so as to easily complex the free transition metal ions. Summary of the invention
[0006] The current lithium battery positive electrode has transition metal ions dissolved, which will cause serious Li + / Ni 2+The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a positive electrode sheet and a preparation method thereof, and a lithium ion battery that can inhibit the dissolution of transition metals.
[0007] The technical solution of the present invention is as follows:
[0008] On the one hand, the present invention provides a positive electrode sheet capable of inhibiting the dissolution of transition metals, comprising a positive electrode collector and a slurry disposed on the positive electrode collector, wherein the slurry comprises tubular halloysite, a positive electrode material, a conductive agent, a binder and a solvent.
[0009] Preferably, the mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent is 1-5: 230-250: 35-45: 35-45: 550-800.
[0010] Preferably, the mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent is 2-4: 235-245: 38-42: 38-42: 650-700.
[0011] Preferably, the positive electrode material is LiNi 0.60 Mn 0.2 Co 0.2 O2, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.
[0012] On the other hand, the present invention provides a method for preparing a positive electrode sheet capable of inhibiting the dissolution of transition metals, comprising the following steps:
[0013] Dispersing the tubular halloysite, the positive electrode material, the conductive agent, and the binder in a solvent, and mixing them evenly to obtain a slurry;
[0014] The slurry is coated on a positive electrode current collector and dried to obtain a positive electrode sheet capable of inhibiting the dissolution of transition metals.
[0015] Preferably, the preparation method further comprises the step of pre-treating the tubular halloysite:
[0016] The tubular halloysite is placed in distilled water and stirred evenly, and diluted hydrochloric acid is continuously added and stirred evenly to obtain a suspension; the suspension is subjected to ultrasonic oscillation, and after standing, the supernatant is centrifuged to separate the precipitate, and the suspension is washed with distilled water until neutral, and dried to obtain the treated tubular halloysite.
[0017] Preferably, in the tubular halloysite pretreatment step, the ratio of tubular halloysite to distilled water is 0.5-1.5 mg: 20-50 mL, the mass fraction concentration of dilute hydrochloric acid is 1-3%, and the ratio of tubular halloysite to dilute hydrochloric acid is 0.5-1.5 mg: 1-3 mL.
[0018] Preferably, in the tubular halloysite pretreatment step, the dilute hydrochloric acid is added and stirred for 1 to 3 hours at a stirring speed of 200 to 500 rpm; the duration of the ultrasonic oscillation is 30 to 50 minutes, the speed of the centrifugal separation is 8000 to 12000 rpm, the drying temperature is 150 to 180° C., and the drying time is 12 to 24 hours.
[0019] Preferably, in the preparation method, the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent are stirred at a rotation speed of 300 to 800 rpm at room temperature for 12 to 24 hours to obtain the slurry;
[0020] The slurry is coated on a positive electrode current collector, and vacuum dried at 70 to 80° C. for 8 to 12 hours to obtain a positive electrode sheet capable of inhibiting the dissolution of transition metals.
[0021] In another aspect, the present invention provides a lithium-ion battery, comprising any one of the above-mentioned positive electrode sheets or a positive electrode sheet obtained by any one of the above-mentioned preparation methods.
[0022] The present invention has at least one of the following beneficial effects:
[0023] The present invention forms a positive electrode sheet with the ability to inhibit the dissolution / crosstalk of transition metal ions by adding natural one-dimensional nano-tubular clay mineral tubular halloysite (HNT) as a positive electrode additive into the preparation process of high-nickel positive electrode materials. Tubular halloysite (HNT) has a large specific surface area, inner and outer surfaces with different reactivity, and a unique hollow tubular structure. The positive electrode sheet containing HNT of the present invention has a negatively charged outer wall, which can provide sufficient active sites to promote the rapid transmission of lithium ions. At the same time, it has a high specific surface area and a strong metal ion adsorption capacity, and can chelate the dissolved transition metal ions to prevent the occurrence of a series of side reactions caused by their shuttling between positive and negative, thereby achieving long-term stable battery circulation.
[0024] The process of the invention is simple and effective; the clay mineral used is green, safe, low-priced and abundant in yield, and has industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of HNT after being treated in step a of Example 1 of the present invention.
[0026] Figure 2 This is a scanning electron microscope image of the HNT-containing positive electrode material prepared in Example 1 of the present invention.
[0027] Figure 3 LiNi is the positive electrode material used in Example 1 of the present invention. 0.60 Mn 0.2 Co 0.2Comparison of X-ray diffraction patterns of O2 and HNT-containing cathode materials.
[0028] Figure 4 The LiNi used in Example 1 of the present invention 0.60 Mn 0.2 Co 0.2 Comparison of the current-voltage curves of O2 positive electrode material (left) and HNT-containing positive electrode material (right).
[0029] Figure 5 This is a comparison chart of the cycle curves of the Li||HNT-NCM622 batteries prepared in Examples 1, 2, and 3 of the present invention and the battery prepared in Comparative Example 1.
[0030] Figure 6 This is a comparison chart of the cycle curves of the Li||HNT-NCM622 battery prepared in Example 2 of the present invention and the batteries prepared in Comparative Examples 3 and 4.
[0031] Figure 7 The positive electrode material LiNi containing HNT prepared in Example 2 of the present invention 0.60 Mn 0.2 Co 0.2 O2 and lithium negative electrode are matched and assembled into a battery and the positive electrode material LiNi without HNT prepared in Comparative Example 1 0.60 Mn 0.2 Co 0.2 A comparison chart of the long cycle of batteries assembled with O2 and lithium negative electrodes at 55°C.
[0032] Figure 8 LiNi used in Example 2 of the present invention 0.60 Mn 0.2 Co 0.2 Comparison of differential capacitance curves of O2 positive electrode material (left) and HNT-containing positive electrode material (right).
[0033] Fig. 9 This is a comparison chart of the transition metal ion content on the lithium metal negative electrode side prepared in Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0034] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] An embodiment of the present invention provides a positive electrode sheet capable of inhibiting dissolution of transition metals, comprising a positive electrode current collector and a slurry disposed on the positive electrode current collector, wherein the slurry comprises tubular halloysite, a positive electrode material, a conductive agent, a binder and a solvent.
[0036] The present invention forms a positive electrode sheet with the ability to inhibit the dissolution / crosstalk of transition metal ions by adding natural one-dimensional nano-tubular clay mineral tubular halloysite (HNT) as a positive electrode additive into the preparation process of high-nickel positive electrode materials. Tubular halloysite (HNT) has a large specific surface area, inner and outer surfaces with different reactivity, and a unique hollow tubular structure. The positive electrode sheet containing HNT of the present invention has a negatively charged outer wall, which can provide sufficient active sites to promote the rapid transmission of lithium ions. At the same time, it has a high specific surface area and a strong metal ion adsorption capacity, and can chelate the dissolved transition metal ions to prevent the occurrence of a series of side reactions caused by their shuttling between positive and negative, thereby achieving long-term stable battery circulation.
[0037] In some embodiments, the mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent is 1-5: 230-250: 35-45: 35-45: 550-800.
[0038] In some embodiments, the mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent is 2-4: 235-245: 38-42: 38-42: 650-700.
[0039] Specifically, the mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent can be 1:230:35:35:550, 1:240:40:40:600, 1:240:40:40:700, 1:240:40:40:800, 2:240:40:40:600, 2:240:40:40:700, 2:240:40:40:750, 2:240:40:40:800, 3:240:40:40:600, 3:240:40:40:700. 0:40:650, 3:240:40:40:700, 3:240:40:40:750, 4:240:40:40:600, 4:240:40:40:650, 4:240:40:40:700, 4:240:40:40:800, 5:230:35:35:550, 5:240:40:40:600, 5:240:40:40:650, 5:240:40:40:700 or 5:240:40:40:800, etc.
[0040] In some embodiments, the positive electrode material is LiNi 0.60 Mn 0.2 Co 0.2 O2.
[0041] In some embodiments, the binder is polyvinylidene fluoride.
[0042] In some embodiments, the conductive agent is conductive carbon black.
[0043] In some embodiments, the solvent is N-methylpyrrolidone.
[0044] Another embodiment of the present invention provides a method for preparing a positive electrode sheet capable of inhibiting the dissolution of transition metals, comprising the following steps:
[0045] a. pre-treating the tubular halloysite;
[0046] b. The tubular halloysite in step a and the positive electrode material, the conductive agent, and the binder are dispersed in a solvent and mixed uniformly to obtain a slurry;
[0047] c. Apply the slurry in step b on the positive electrode current collector, and evenly apply the electrode slurry on the aluminum foil using a coater, vacuum dry at 70-80°C for 8-12h, and cut into the required size with a cutting machine to obtain a positive electrode sheet that can inhibit the dissolution of transition metals.
[0048] The process of the invention is simple and effective; the clay mineral used is green, safe, low-priced and abundant in yield, and has industrial prospects.
[0049] In some embodiments, the pretreatment step in step a includes: placing the tubular halloysite in distilled water and stirring evenly, adding dilute hydrochloric acid under a certain shear force and stirring thoroughly, then placing the suspension in an ultrasonic cleaner for ultrasonic oscillation, oscillating until the tubular halloysite particles are fully dispersed, standing for a certain period of time, taking the supernatant and centrifuging to remove the precipitate, washing with distilled water until neutral, and drying.
[0050] In a specific embodiment, in step a, the tubular halloysite is placed in distilled water and stirred evenly, and after being evenly mixed, the mixture is stirred at a speed of 200 to 500 rpm for 1 to 3 hours, and then dilute hydrochloric acid is added dropwise, and then the suspension is placed in an ultrasonic cleaner for ultrasonic oscillation for 30 to 50 minutes, the supernatant is centrifuged at 8000 to 12000 rpm to separate the precipitate, and the solution is repeatedly washed with distilled water for more than 3 times until the solution is neutral, and then placed in a vacuum oven at 150 to 180° C. and dried for 12 to 24 hours;
[0051] In some embodiments, in step a, the ratio of tubular halloysite to distilled water is 0.5-1.5 mg:20-50 mL, specifically 0.5 mg:20 mL, 0.5 mg:30 mL, 0.5 mg:35 mL, 0.5 mg:40 mL, 0.5 mg:45 mL, 0.5 mg:50 mL, 1 mg:20 mL, 1 mg:25 mL, 1 mg:30 mL, 1 mg:35 mL, 1 mg:40 mL, 1 mg:50 mL, 1.5 mg:20 mL, 1.5 mg:25 mL, 1.5 mg:30 mL, 1.5 mg:35 mL, 1.5 mg:40 mL or 1.5 mg:50 mL, etc.
[0052] In some embodiments, in step a, the mass fraction concentration of dilute hydrochloric acid is 1-3%, specifically 1%, 1.5%, 2%, 2.5% or 3%.
[0053] In some embodiments, in step a, the ratio of tubular halloysite to dilute hydrochloric acid is 0.5-1.5 mg:1-3 mL, specifically 0.5 mg:1 mL, 0.5 mg:2 mL, 0.5 mg:3 mL, 1 mg:1 mL, 1 mg:2 mL, 1 mg:3 mL, 1.5 mg:1 mL, 1.5 mg:2 mL or 1.5 mg:3 mL, etc.
[0054] In some embodiments, in step a, the stirring speed is 200-500 rpm, and the stirring time is 1-3 h. The stirring speed can be specifically 200 rpm, 300 rpm, 400 rpm or 500 rpm, and the stirring time can be specifically 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc.
[0055] In some embodiments, in step a, the duration of ultrasonic oscillation is 30 to 50 minutes, specifically 30 minutes, 35 minutes, 40 minutes, 45 minutes or 50 minutes.
[0056] In some embodiments, in step a, the centrifugal speed is 8000-12000 rpm, specifically 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm or 12000 rpm, etc.
[0057] In some embodiments, in step a, the mixture is placed in a vacuum oven and dried at 150-180°C for 12-24 hours. The drying temperature can be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, etc., and the drying time can be 12h, 14h, 15h, 16h, 18h, 19h, 20h, 22h or 24h, etc.
[0058] In some embodiments, in step b, stirring is carried out at room temperature at a speed of 300-800 rpm for 12-24 h, and the speed can be specifically 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm, and the stirring time can be specifically 12 h, 14 h, 15 h, 16 h, 18 h, 20 h, 22 h, 23 h or 24 h, etc.
[0059] In some embodiments, in step c, vacuum drying is performed at 70-80°C for 8-12 hours. The drying temperature can be 70°C, 72°C, 74°C, 75°C, 76°C, 78°C or 80°C, etc., and the drying time can be 8h, 9h, 10h, 11h or 12h, etc.
[0060] In some embodiments, in step c, the electrode slurry is evenly coated on the aluminum foil using a coater, dried, and cut into the required size using a cutting machine for subsequent battery assembly.
[0061] The present invention adds nano-tubular clay mineral HNT to the positive electrode material LiNi 0.60 Mn 0.2 Co 0.2 In O2, a positive electrode sheet that can inhibit the dissolution of transition metals and prevent the crosstalk between the positive and negative electrodes is designed by mixing with conductive agent, binder polyvinylidene fluoride and N-methylpyrrolidone in a certain proportion. This positive electrode sheet containing a small amount of clay minerals can prevent the transition metal from dissolving and catalyzing the electrolyte to produce a series of side reactions, further preventing the phase change and microcracks of the positive electrode material, or shuttling to the lithium metal negative electrode to destroy the generated interface. This positive electrode sheet containing HNT improves the long-term cycle stability of high-nickel positive electrode materials to a certain extent.
[0062] Another embodiment of the present invention provides a lithium-ion battery, comprising any one of the above-mentioned positive electrode sheets or a positive electrode sheet obtained by any one of the above-mentioned preparation methods.
[0063] The positive electrode sheet of the lithium-ion battery obtained by the present invention can prevent the transition metal from dissolving and catalyzing the electrolyte to produce a series of side reactions, further preventing the phase change and microcracks of the positive electrode material, or shuttling to the lithium metal negative electrode to destroy the generated interface, thereby achieving long-term stable cycle of the battery.
[0064] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, an electrolyte, and a separator.
[0065] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode slurry, the negative electrode slurry includes a negative electrode active material, a conductive agent, a thickener and a binder, and the negative electrode active material includes one or more of artificial graphite, natural graphite, soft carbon, hard carbon, secondary carbon microbeads, and silicon-based materials.
[0066] In some embodiments, the electrolyte includes a lithium salt and an organic solvent, the lithium salt includes one or more of lithium hexafluorophosphate and lithium perchlorate, and the organic solvent includes one or more of cyclic carbonate, chain carbonate, and carboxylate.
[0067] In some embodiments, the separator is at least one of a glass fiber separator, a polytetrafluoroethylene separator, a polypropylene separator, a polyethylene separator, and a cellulose separator.
[0068] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0069] The following HNTs were purchased from Aladdin Reagent Company, CAS No.: 1332-58-7; the following cathode materials LiNi 0.60 Mn 0.2 Co 0.2 O2 was purchased from CLUDE Technology Co., Ltd.
[0070] Example 1
[0071] Step a: First, 1 mg of HNT was weighed with an electronic balance and placed in 20 mL of distilled water and stirred for 1 hour until the solution was evenly dispersed. 1 mL of 1% dilute hydrochloric acid was added dropwise at 300 rpm and stirred thoroughly. Then, the suspension was placed in an ultrasonic cleaner for ultrasonic oscillation for 30 minutes. The supernatant was centrifuged at 8000 rpm to separate the precipitate. The solution was repeatedly washed with distilled water for more than 3 times until the solution was neutral, and then placed in a vacuum oven at 180°C for 12 hours.
[0072] Step b: Then weigh the dried HNT and the positive electrode material LiNi 0.60 Mn 0.2 Co 0.2 O2, conductive carbon black, binder polyvinylidene fluoride, and N-methylpyrrolidone are mixed in a mass ratio of 1mg:240mg:40mg:40mg:550mg, stirred at 500rpm for 12h at room temperature to obtain a pole piece slurry;
[0073] Step c: Finally, the electrode slurry is evenly coated on the aluminum foil using a coater, vacuum dried at 75°C for 10 hours, cut into the required size by a cutting machine, and assembled into button batteries in an argon glove box with a water and oxygen content of less than 0.1ppm using a lithium metal negative electrode, a polypropylene separator, and an electrolyte 1M LiPF6 in EC / EMC (3:7).
[0074] Example 2
[0075] The other experimental steps are the same as those in Example 1. The only difference from Example 1 is that the material components are shown in Table 1:
[0076] Table 1 Material composition of Example 2
[0077]
[0078] Example 3
[0079] The other experimental steps are the same as those in Example 1. The only difference from Example 1 is that the material components are shown in Table 2:
[0080] Table 2 Material components of Example 3
[0081]
[0082] Example 4
[0083] The other experimental steps are the same as those in Example 1. The only difference from Example 1 is that the material components are shown in Table 3:
[0084] Table 3 Material components of Example 4
[0085]
[0086] Example 5
[0087] The other experimental steps are the same as those in Example 1. The only difference from Example 1 is that the material components are shown in Table 4:
[0088] Table 4 Material composition of Example 5
[0089]
[0090] Example 6
[0091] The other experimental steps are the same as those in Example 1, except that the pretreatment step of HNT in step a is different from that in Example 1:
[0092] First, 1 mg of HNT was weighed with an electronic balance and placed in 35 mL of distilled water and stirred for 2 h until the solution was evenly dispersed. 2 mL of 1% dilute hydrochloric acid was added dropwise at 200 rpm and stirred thoroughly. The suspension was then placed in an ultrasonic cleaner for ultrasonic oscillation for 40 min. The supernatant was centrifuged at 10,000 rpm to separate the precipitate. The solution was repeatedly washed with distilled water for more than 3 times until the solution was neutral and then placed in a vacuum oven at 170°C for 15 h.
[0093] Example 7
[0094] The other experimental steps are the same as those in Example 1, except that the pretreatment step of HNT in step a is different from that in Example 1:
[0095] First, 1 mg of HNT was weighed with an electronic balance and placed in 50 mL of distilled water and stirred for 2 h until the solution was evenly dispersed. 3 mL of 1% dilute hydrochloric acid was added dropwise at 500 rpm and stirred thoroughly. The suspension was then placed in an ultrasonic cleaner for ultrasonic oscillation for 50 min. The supernatant was centrifuged at 12000 rpm to separate the precipitate. The solution was repeatedly washed with distilled water for more than 3 times until the solution was neutral and dried in a vacuum oven at 150°C for 24 h.
[0096] Example 8
[0097] The other experimental steps are the same as those in Example 1, except that the processing parameters of steps b and c are different:
[0098] Step b: Stir at 300 rpm for 24 h at room temperature.
[0099] Step c: vacuum drying at 70°C for 12 h.
[0100] Example 9
[0101] The other experimental steps are the same as those in Example 1, except that the processing parameters of steps b and c are different:
[0102] Step b: Stir at 800 rpm for 12 h at room temperature.
[0103] Step c: vacuum drying at 80°C for 8 h.
[0104] Comparative Example 1
[0105] The other experimental steps are the same as those in Example 1, except that no HNT is added.
[0106] Comparative Example 2
[0107] The other experimental steps are the same as those in Example 1, except that the HNT is not subjected to the pretreatment of step a, and steps b and c are directly carried out.
[0108] Comparative Example 3
[0109] The other experimental steps were the same as those in Example 1, except that the amount of HNT added was 0.5 mg.
[0110] Comparative Example 4
[0111] The other experimental steps were the same as those in Example 1, except that the amount of HNT added was 6 mg.
[0112] The following tests were performed on the positive electrode sheets and batteries in the examples and comparative examples, and the results were as follows:
[0113] Figure 1is a scanning electron microscope image of HNT after treatment in step a of Example 1. Figure 1 Scanning electron microscope images show that HNT has a hollow rod-like structure. 0.60 Mn 0.2 Co 0.2 After O2, conductive carbon black, binder polyvinylidene fluoride, and N-methylpyrrolidone were uniformly mixed according to the proportions in Example 1, the scanning electron microscope image of the obtained electrode was as follows: Figure 2 As shown, HNTs are dispersed more evenly around the positive electrode material.
[0114] Figure 3 The original cathode material LiNi 0.60 Mn 0.2 Co 0.2 X-ray diffraction patterns of O2 and Example 1 after adding HNT. Figure 3 As shown in the figure, before and after the addition of HNT, the NCM material still belongs to the R / 3m space layered α-NaFeO2 structure, and no new diffraction peaks appear in the XRD full spectrum, indicating that the NCM does not produce impurities before and after the addition of HNT. At the same time, the characteristic peaks such as (003) and (104) are clear and distinct, and the diffraction angle does not shift, proving that the addition of HNT does not affect the crystal structure of the NCM material.
[0115] Figure 4 The test was conducted by cyclic voltammetry at different scan rates (0.2, 0.3, 0.4, 0.5 mV / s). The test results showed that the redox potential difference of NCM after adding HNT in Example 1 was only 0.223 V, while that of the control group without adding HNT was 0.449 V, which was twice that of the experimental group. The results showed that the negative charge on the surface of HNT had "lithium affinity", which could promote the transport and migration of lithium ions and improve the transport kinetics of lithium ions.
[0116] By adjusting the ratio of HNT, the transition metal ion chelation ability and ion / electronic conductivity of the material will be affected, thus affecting the electrochemical performance of the battery. Therefore, we optimized the ratio through multiple sets of experiments. Figure 5 The long cycle curve of the full-electric battery assembled under the ratio of Examples 1, 2, and 3 is obtained by calculation. The control group (Comparative Example 1) without adding HNT has a capacity decay of 51.6% after 400 cycles. Figure 5As shown, after adding 1 mg HNT (Example 1), the battery capacity retention rate of 400 cycles can reach 62.2%, and after adding 3 mg HNT (Example 2), the battery capacity retention rate of 400 cycles is increased to 72.7%. The reason is that HNT can anchor the highly active nickel ions on the surface of the NCM material, reduce the adverse interface side reactions between the positive electrode / electrolyte, improve the cycle stability of the material, and achieve excellent electrochemical performance. The amount of HNT added is further increased to 5 mg (Example 3). The capacity retention rate of Example 3 has decreased to 66.8%, but its capacity retention rate is still higher than that of the control group (Comparative Example 1) to which HNT is not added. The reason is that HNT is non-conductive, and too much HNT will affect the transmission capacity of electrons to a certain extent, thereby affecting the electrochemical performance of the battery. In summary, under the ratio of Example 2, the electrochemical performance of the obtained battery is the most superior.
[0117] Figure 6 The following is a comparison chart of the cycle curves of the Li||HNT-NCM622 battery prepared in Example 1 and the batteries prepared in Comparative Examples 3 and 4. Figure 6 It can be seen that the capacity decay amplitude of Comparative Examples 3 to 4 after 400 cycles is significantly greater than that of Example 2, which further illustrates that the amount of HNT added will affect the electrochemical performance of the battery.
[0118] The battery assembled from Example 2 and Comparative Example 1 was subjected to charge and discharge tests at 55°C. Figure 7 The battery cycle performance diagram. High temperature conditions will intensify the dissolution of transition metal ions. It can be clearly concluded that under high temperature conditions, the cycle performance of the positive electrode sheet with HNT added is better than that of the control group without HNT added (Comparative Example 1). After 300 cycles, the battery capacity retention rate of Example 2 reached 64.2%, while that of the control group without HNT added (Comparative Example 1) was only 46.5%.
[0119] In order to further explore the effect of adding HNT on the cycle performance of NCM materials, the positive electrode material LiNi used in Example 2 of the present invention was 0.60 Mn 0.2 Co 0.2 The dQ / dV curves of different cycles of O2 and HNT-containing positive electrode materials during charge and discharge cycles are analyzed. During the battery charge and discharge process, the structural degradation of the electrode material and the dissolution of transition metal ions are reflected in the redox peak slowly shifting to a low potential until it disappears, indicating that the lithium-nickel mixing phenomenon in the NCM material is serious, causing the material to gradually transform from a layered phase to a rock salt phase, forming an electrochemically inert NiO phase. Figure 8As shown, the potential shift of the positive electrode material with added HNT is only 71.6 mV, but the electrochemical shift of the control group without added HNT is as high as 226 mV, indicating that the positive electrode material with added HNT exhibits better structural reversibility, further proving that HNT can effectively inhibit the structural degradation caused by the dissolution of transition metal ions and improve the cycle stability of the material.
[0120] Fig. 9 The transition metal ion content on the lithium metal surface after 400 cycles of Example 2 and Comparative Example 1 shows that HNT significantly inhibits the dissolution of transition metal ions on the positive electrode side and reduces the shuttle of transition metal ions to the lithium metal negative electrode side after dissolution.
[0121] The transition metal ion content on the surface of lithium metal in Examples 1 to 9 and Comparative Examples 1 to 4 after 400 cycles was measured.
[0122] The determination method is: using inductively coupled plasma technology (ICP-OES) to determine the transition metal (TM) content dissolved in the lithium metal anode after cycling. Sample preparation method: disassemble the button battery after 100 cycles, take out the lithium metal anode, dissolve it in 10ml of frozen distilled water, and after the solution passes through a 0.45μm water filter membrane, an ICP-OES test sample is prepared, and the prepared sample is placed in the ICP-OES instrument for testing and determination of Mn / Ni elements.
[0123] The measurement results are shown in Table 5.
[0124] Table 5
[0125]
[0126]
[0127] It can be seen from Table 5 that the transition metal ion content on the lithium metal surface of Examples 1 to 9 after 400 cycles is significantly lower than that of Comparative Example 1 (no HNT added), Comparative Example 2 (HNT not pre-treated), Comparative Example 3 (HNT addition amount 0.5 mg) and Comparative Example 4 (HNT addition amount 6 mg), indicating that not adding HNT, not pre-treating HNT, and adding too much or too little HNT will affect the transition metal ion content on the lithium metal surface.
[0128] In summary, the present invention adds natural one-dimensional nanotubular clay mineral HNT as a positive electrode additive in the preparation process of high-nickel positive electrode materials. By selectively adding an appropriate amount of HNT and pre-treating the HNT, a positive electrode sheet with the function of inhibiting the dissolution / crosstalk of transition metal ions is formed. The dissolved transition metal ions can be chelated to prevent a series of side reactions caused by their shuttling between positive and negative electrodes, thereby achieving long-term stable battery cycling.
[0129] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A positive electrode sheet capable of inhibiting the dissolution of transition metals, comprising a positive electrode current collector and a slurry disposed on the positive electrode current collector, characterized in that: The slurry includes tubular halloysite, a positive electrode material, a conductive agent, a binder and a solvent.
2. A positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 1, characterized in that: The mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent is 1-5: 230-250: 35-45: 35-45: 550-800.
3. The positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 1, characterized in that: The mass ratio of the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent is 2-4: 235-245: 38-42: 38-42: 650-700.
4. The positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 1, characterized in that: The positive electrode material is LiNi 0.60 Mn 0.2 Co 0.2 O2, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.
5. A method for preparing a positive electrode sheet capable of inhibiting the dissolution of transition metals, characterized in that: The following steps are involved: Dispersing the tubular halloysite, the positive electrode material, the conductive agent, and the binder in a solvent, and mixing them evenly to obtain a slurry; The slurry is coated on a positive electrode current collector and dried to obtain a positive electrode sheet capable of inhibiting the dissolution of transition metals.
6. The method for preparing a positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 5, characterized in that: The preparation method further comprises the step of pre-treating the tubular halloysite: The tubular halloysite is placed in distilled water and stirred evenly, and diluted hydrochloric acid is continuously added and stirred evenly to obtain a suspension; the suspension is subjected to ultrasonic oscillation, and after standing, the supernatant is centrifuged to separate the precipitate, and the suspension is washed with distilled water until neutral, and dried to obtain the treated tubular halloysite.
7. The method for preparing a positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 6, characterized in that: In the tubular halloysite pretreatment step, the ratio of tubular halloysite to distilled water is 0.5-1.5 mg: 20-50 mL, the mass fraction concentration of dilute hydrochloric acid is 1-3%, and the ratio of tubular halloysite to dilute hydrochloric acid is 0.5-1.5 mg: 1-3 mL.
8. The method for preparing a positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 6, characterized in that: In the tubular halloysite pretreatment step, the dilute hydrochloric acid is added at a stirring speed of 200 to 500 rpm and stirred for 1 to 3 hours; the duration of the ultrasonic oscillation is 30 to 50 minutes, the rotation speed of the centrifugal separation is 8000 to 12000 rpm, the drying temperature is 150 to 180° C., and the drying time is 12 to 24 hours.
9. The method for preparing a positive electrode sheet capable of inhibiting dissolution of transition metals according to claim 5, characterized in that: In the preparation method, the tubular halloysite, the positive electrode material, the conductive agent, the binder and the solvent are stirred at a rotation speed of 300 to 800 rpm at room temperature for 12 to 24 hours to obtain the slurry; The slurry is coated on a positive electrode current collector, and vacuum dried at 70 to 80° C. for 8 to 12 hours to obtain a positive electrode sheet capable of inhibiting the dissolution of transition metals.
10. A lithium ion battery, characterized in that: The invention comprises the positive electrode sheet described in any one of claims 1 to 4 or the positive electrode sheet obtained by the preparation method described in any one of claims 5 to 9.
Citation Information
Patent Citations
Preparation method of high-performance positive electrode material for inhibiting dissolution of transition metal ions of lithium ion battery positive electrode material
CN111200128A